2000
DOI: 10.1080/10473289.2000.10464010
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the LPG Vehicles Program in the Metropolitan Area of Mexico City

Abstract: The environmental agency in the metropolitan area of Mexico City has launched a program to introduce more energy-efficient modes of transport, one of which is the use of alternative and less polluting fuels. With the perspective in mind, a liquefied petroleum gas (LPG) fleet of vehicles is exempt of the mandatory "one day without a car" program if the emission of pollutants is below the standard authorized for that specific purpose. Today, about 28,000 light-duty vehicles and heavy-duty trucks circulate in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although LPG powered vehicles represent less than 1% of the total fleet, they should also be considered important sources. Schifter et al (2000) evaluated the LPG vehicles program implemented in Mexico City and found that 95% of them have emissions that exceed those required by environmental regulations. The LPG fleet is composed mainly by vehicles used intensively (light and heavy duty trucks, and small buses with a 20 passenger capacity).…”
Section: Comparison Of Ambient Voc Concentrations To Vehicles Exhaustmentioning
confidence: 99%
“…Although LPG powered vehicles represent less than 1% of the total fleet, they should also be considered important sources. Schifter et al (2000) evaluated the LPG vehicles program implemented in Mexico City and found that 95% of them have emissions that exceed those required by environmental regulations. The LPG fleet is composed mainly by vehicles used intensively (light and heavy duty trucks, and small buses with a 20 passenger capacity).…”
Section: Comparison Of Ambient Voc Concentrations To Vehicles Exhaustmentioning
confidence: 99%
“…Although LPG powered vehicles represent less than 1% of the total fleet, they are also important emission sources. The LPG fleet is composed mainly of vehicles used intensively (light and heavy duty trucks, and microbuses with 20-passenger capacity); 95% of them have emissions that exceed the standards required by local environmental regulations (Schifter et al, 2000). The LPG leaked from households at nighttime accumulates in the shallow unstable boundary layer and adds to the morning emissions from traffic and from LPG transmission systems.…”
Section: Vertical Distribution Of Vocsmentioning
confidence: 99%
“…1% of the total fleet, they are also important sources. The LPG fleet is composed mainly of vehicles used intensively (light and heavy duty trucks, and microbuses with 20-passenger capacity); 95% of them have emissions that exceed those required by local environmental regulations (Schifter et al, 2000). The LPG leaked at nighttime from households accumulates in the shallow unstable boundary layer and adds to the morning emissions from traffic and from LPG transmission systems.…”
Section: Egumentioning
confidence: 99%